2002
DOI: 10.1039/b205367e
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of dealuminated faujasites for adsorption of volatile organic compounds

Abstract: A series of dealuminatead faujasitic zeolites, obtained from the ammonium form of Y zeolite, was prepared by two different methodologies: a relatively common self-steaming method, where temperatures in the range 813 to 1093 K were used, and a less well studied solid-state dealumination method using ammonium hexafluorosilicate, which employed a lower temperature (453 K) than those used in the self-steaming method. It was possible to obtain samples by solid-state dealumination with both high levels of dealuminat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 18 publications
1
15
0
Order By: Relevance
“…Gas removal methods via adsorption onto solids are typically based on activated carbon, even though regeneration is difficult for this adsorbent, thermal instability poses fire risks, pore clogging may occur, and hygroscopicity must be considered. 96,118,[120][121][122][123][124] Reported adsorption capacities of a variety of adsorbents investigated for VOCs, NOx, and SOx encapsulation are listed in Table 4. Adsorption of VOCs, NOx, and SOx gases onto inorganic solids is mostly focused on zeolites, which are often considered to be a more robust alternative to activated carbon.…”
Section: The Removal Of Volatile Organic Compounds (Vocs) Nitrogen Omentioning
confidence: 99%
See 2 more Smart Citations
“…Gas removal methods via adsorption onto solids are typically based on activated carbon, even though regeneration is difficult for this adsorbent, thermal instability poses fire risks, pore clogging may occur, and hygroscopicity must be considered. 96,118,[120][121][122][123][124] Reported adsorption capacities of a variety of adsorbents investigated for VOCs, NOx, and SOx encapsulation are listed in Table 4. Adsorption of VOCs, NOx, and SOx gases onto inorganic solids is mostly focused on zeolites, which are often considered to be a more robust alternative to activated carbon.…”
Section: The Removal Of Volatile Organic Compounds (Vocs) Nitrogen Omentioning
confidence: 99%
“…However, flammability and regeneration represent serious drawbacks, which may be circumvented by the use of zeolites, since these exhibit high thermal stability and can typically be regenerated easily. 4 Many different zeolites have been investigated for the removal of VOCs from gas streams, including faujasite-type, 122,123,132 A-type, 96 and Y-type zeolites, 120,124,133 as well as heulandite, 134 118,124 and SBA-15. 118 In general, the use of zeolites for the adsorption of VOCs is beneficial for dry gas streams, since zeolites are usually hydrophilic.…”
Section: The Removal Of Volatile Organic Compounds (Vocs) Nitrogen Omentioning
confidence: 99%
See 1 more Smart Citation
“…It was found that the component having the higher molecular weight adsorbed preferentially over the other, except in the case of MEK-toluene mixture adsorption on ZSM-5, where toluene was believed to be excluded due to steric effects. Pires et al [5] studied the effect of dealumination of zeolite Na-Y on the sorption of MEK at 298 K, and showed that an increase in the percentage of dealumination reduced MEK adsorption, suggesting that sodium cations favor MEK. Uguina et al [6] studied MEK desorption from silicalite and activated carbon beds, and suggested that the regeneration temperature for silicalite was in the range of 90-170 • C, whereas in the case of activated carbon it was found to be within the range of 150-240 • C. These findings suggest that dispersion interactions might be dominant in the case of silicalite, and electrostatic interactions might be the dominant ones in the case of activated carbon due to the presence of acid sites.…”
Section: Introductionmentioning
confidence: 98%
“…9) Therefore, novel adsorbents superior to the heat resistance and regeneration characteristics as compared with activated carbon have been desired. As representative candidates for the novel adsorbents, zeolite, 2,3,1012) silica gel, 13,14) mesoporous silica, 1527) and super-microporous silica (SMPS) 28) have been studied. Zeolite has micropores and indicates relatively high VOC dynamic adsorption properties, however, it is necessary to treat it at high temperatures for regeneration because the aromatic hydrogens of toluene interact with the zeolite framework oxygen atoms that are Lewis basic sites.…”
Section: Introductionmentioning
confidence: 99%